Fictions of Migration: Narratives of Displacements in Peru and Bolivia. - Molina Ergueta, Mary Carmen (Imagofagia, 2021)
Sobre Lorena Cuya Gavilano. Fictions of Migration: Narratives of Displacements in Peru and Bolivia. Ohio: The Ohio State University Press, 2021, 228 pp., ISBN 978-0814214657.